The Impact of Organizational Flexibility on Sustainable Marketing Strategies: A Field Study in Private Universities in Latakia Province. (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research mainly aims to show the impact of organizational flexibility on sustainable marketing strategies in private universities in Latakia Governorate. The researcher relied on the descriptive and analytical approach. In the theoretical section, the concept of organizational flexibility and its importance was addressed, and its dimensions (operational flexibility, strategic flexibility, Tactical flexibility) and clarifying the concept of each of them. The researcher also touched on the concept of sustainable marketing strategies and their importance. As for the practical section, observation and personal interviews were relied upon. A questionnaire consisting of 24 statements was designed and the SPSS23 program was relied upon to analyze the data and test the hypotheses. The study reached the following conclusions: Several results, the most important of which is the presence of a good positive moral effect of organizational flexibility on sustainable marketing strategies in the study.